Enhanced antibacterial effect and biodegradation of coating via dual-in-situ growth based on carboxymethyl cellulose. (15th February 2023) - Lin, Zhenhao; Fu, Hao; Zhang, Yuancheng; Deng, Yongfu; Wei, Fuxiang; Li, Hao; Xu, Chuanhui; Hua, Fuli; Lin, Baofeng
Abstract: The lack of antimicrobial effect of commercial paper coating for food packaging makes it difficult to prevent food spoilage and harms the environment by non-biodegradation. Herein, carboxymethyl cellulose (CMC) provides negatively charged sites for anchoring Ag + and Zn 2+ to grow AgNPs and ZIF-8 in situ on its molecular chains. The ZIF-8/AgNPs@CMC paper coating has excellent synergistic antibacterial activity to prolong the shelf-life of food. It not only has good thermal stability but binds closely to the paper and its adhesion force reaches 628.9 nN. Besides, the ZIF-8/AgNPs@CMC coated paper has better mechanical properties, water vapor barrier, and resists water solubility. Interestingly, due to the confinement effect of ZIF-8, the cumulative release of AgNPs after 168 h is only 2.66 % to avoid possible food safety risks. Especially, the coating can be almost biodegraded in the soil after 30 days, which provides the possibility to replace the non-biodegradable coatings in food packaging. Graphical abstract: Preparation and application process of the ZIF-8/AgNPs@CMC paper coating. Unlabelled Image Highlights: Carboxymethyl cellulose provided negatively charged sites to grow ZIF-8 in situ. Carboxymethyl cellulose successfully reduced AgNPs in situ through its reducibility. The coating had an excellent antibacterial effect to prolong the shelf-life of food. The coating was effectively biodegraded to avoid pollution of the environment.